Hallucinogenic mushroom misuse reported to Texas poison centers. Issue 4 (18th May 2020) - Forrester, Mathias B.
Abstract: Background: Hallucinogenic mushrooms are fungi that contain the substance psilocybin. When ingested, psilocybin can induce hallucinations, euphoria, and alterations in the perception of space and time. Ingestion of hallucinogenic mushrooms may result in adverse effects. Objective: The objective of this study was to describe hallucinogenic mushroom misuse reported to poison centers. Methods: Cases were exposures to hallucinogenic mushrooms reported to Texas poison centers during 2000–2018 where the exposure reason was Intentional - Misuse or Intentional - Abuse (combined into the term "misuse" in the study). The distribution of the cases was determined for various factors related to patient demographics, exposure circumstances, management, and outcome. Results: Texas poison centers managed 486 hallucinogenic mushroom misuse exposures. Eighty-five percent of the patients were male; the mean age was 20.9 years (range 12–57 years). The exposure route was ingestion alone in 91% of the cases. Seventy-two percent of the exposures occurred at the patient's own residence. Seventy-one percent of the patients were already at or en route to a healthcare facility when the poison center was contacted, 22% were referred to a healthcare facility by the poison center, and 7% of the patients were managed on-site. The most frequent clinical effects were neurological (72%), cardiovascular (25%), and gastrointestinal (23%). Conclusions: The majority of hallucinogenic mushroom misuse exposures involved adolescents or young adults and were male. Most of the exposures tended to be managed at a healthcare facility. The most common clinical effects tended to be neurological, cardiovascular, and gastrointestinal in nature.